Study skills and utilization of library resources by students of gospel faith mission international comprehensive high school, Ibadan, Nigeria (2015)
The study investigated how teaching of study skills and use of library resources can provoke effective utilization of available information resources in secondary schools. The survey research methodology was adopted for the study while the questionnaire and the experiment were used as data collecting instrument. Using the simple random sampling technique, the senior secondary students were grouped to two. Eighty (80) students were selected for the study. Each group comprised of 40 students i.e. the experimental group and the control group. The questionnaire instrument administration was twice, first as pre-test and later as post-test after subjects had undergone teachings on study skills and use of library resources. The study found out that over 38% of the respondents made use of some study techniques. Furthermore, 75% of students had had study skills training in school. The subjects also affirmed that study skill classes equipped them to effectively use library resources. However, environmental barriers, physical tiredness etc was found to have constituted hindrance to students not using the library resources effectively. Similarly, 85% of students affirmed study skills teaching enhanced their academic motivation. The study tested three hypotheses which were rejected and the alternate hypotheses accepted, implying there was a significant difference in all three cases. The study therefore concludes that teaching study skills and library use skills education is helpful and enables library users to effectively use the library resources and therefore recommended that teaching study skills be intensified in all schools at the elementary level.